ASIGNACIÓN DE FUNCIONES EN LA ESCUELA DE FORMACIÓN DE POLICÍAS CBOS SÓCRATES ARBOLEDA SANABRIA DEL CANTÓN BABAHOYO. (LAS PEÑAS) - Gavilanes Villacis, Miriam Marlene (2019)
The management in public institutions regardless of the functions or activities they perform, are organizations linked to the State, which implies that there must be an organization and proper administration of human and material resources, which contribute to the social and human development of the environment in the that they are, so that the processes of administration within the institutions of the state are essential for the development of functions in a systemic way and oriented with the mission of the organization. The present investigation deals with the study made to the administration of the Cbos Police Training School. Socrates Arboleda Sanabria Del Cantón Babahoyo, due to the fact that there have been problems within their work environment, due to the inadequate assignment of functions, which leads to different problems in the development of the internal activities of the organization.